A case study of turn-taking in a meeting - Kaur, Baljit (Journal of Modern Languages, 2017)
This paper presents a case study of the turn-taking patterns that occur in a Parent-Teacher Association (PTA) committee meeting. There has been very little research on proceedings of meetings with participants of various cultures. Such a study is significant in view of the fact that examining turnÂ· taking to such a situation will inevitably add to our general knowledge of how teachers communicate with parents and vice-versa, and by extension, provide insights into the way Malaysians interact to all meeting-like situations.